2004
DOI: 10.1158/0008-5472.can-03-3005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Focal Adhesion Kinase in Acute Myeloid Leukemia Is Associated with Enhanced Blast Migration, Increased Cellularity, and Poor Prognosis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 44 publications
9
113
1
1
Order By: Relevance
“…Finally, analyses of FAK expression levels in esophageal squamous cell carcinoma (Miyazaki et al, 2003), hepatocellular carcinoma (Itoh et al, 2004), acute myeloid leukemia (Recher et al, 2004) and ovarian cancer (Sood et al, 2004) tissue samples have found that FAK expression levels are inversely correlated with patient survival. As many cancer-related deaths are associated with elevated metastatic tumor burden, it is of interest to note that injection of malignant 4T1 cells expressing high levels of FAK led to the early death of 90% of injected animals within 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, analyses of FAK expression levels in esophageal squamous cell carcinoma (Miyazaki et al, 2003), hepatocellular carcinoma (Itoh et al, 2004), acute myeloid leukemia (Recher et al, 2004) and ovarian cancer (Sood et al, 2004) tissue samples have found that FAK expression levels are inversely correlated with patient survival. As many cancer-related deaths are associated with elevated metastatic tumor burden, it is of interest to note that injection of malignant 4T1 cells expressing high levels of FAK led to the early death of 90% of injected animals within 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, these and other factors interact with each other in a complex fashion to determine which blasts will circulate and which will stay in BM. [10][11][12][13] Irrespective of the cause, an increased tendency of blasts to circulate, when defined as the presence of higher blast percentages in PB than in BM, has prognostic value in ALL and MDS. The independent prognostic value of this phenomenon highlights the importance of exploring the causes behind it, and suggests that investigating its underlying causes may help in devising therapeutic strategies.…”
Section: P-valuementioning
confidence: 99%
“…A large number of reports describe an enhanced expression of FAK protein in a variety of human cancers, including sarcomas, astrocytomas and carcinomas of the breast, colon, thyroid, prostate, oral cavity, liver, stomach and ovary (see (McLean et al, 2005) and references herein). Furthermore, FAK overexpression has been correlated with the invasive potential of a tumour and poor patient prognosis Miyazaki et al, 2003;Recher et al, 2004;Sood et al, 2004). In a study of 106 matched pairs of larynx carcinomas and corresponding normal tissue, using immunohistochemistry, we have previously shown a significantly increased expression of FAK at the protein level in both the tumour tissues and the corresponding metastasis (Canel et al, 2006).…”
mentioning
confidence: 99%